Effects of natural colourants on the fatty acids profile of different ice cream formulations - Roriz, Custódio Lobo (2017)
Ice cream is a complex food colloid formed of air bubbles, fat globules, ice crystals and a serum unfrozen phase [1]. Although presenting a complex composition, including milk, sweeteners, emulsifiers, stabilizers, colourants and flavouring agents, ice cream is very poor in some essential components such as natural antioxidants, dietary fibres, minerals and vitamins, all representing features desired by consumers [2]. Nevertheless, the addition of a natural food colourant to ice cream, besides fulfilling its main colouring function, might be an effective way to functionalize it, due to the antioxidant activity of most natural colourants (e.g., anthocyanins, carotenoids or betacyanins). Gomphrena globosa L. is a good example of an alternative source of colouring compounds of natural origin, namely betacyanins, which present a threefold higher colouring capacity than its commercial analogue (anthocyanins), additionally possessing antioxidant, antiviral, and antimicrobial properties [3]. Therefore, betacyanins extracted from the purple flowers of G. globosa were evaluated as colouring/functionalizing agents in icecream formulations, aiming to verify potential improvements on fatty acids profile, analysed by gas chromatography (GC) coupled to a flame ionization detector (FID). In order to acquire comprehensive conclusions, other ice-cream formulations (IF) were prepared and analysed in 5 storage times (ST). Besides the ice cream containing G. globosa extract, three formulations were prepared: control ice cream (without colourants), ice cream with commercial betalain and ice cream with Beta vulgaris extract (E-162). The profiles in fatty acids were especially sensitive to ST, which induced a significant effect in all cases except C18:1 (p=0.271) and MUFA (p=0.108), in contrast with IF, which was only significant in the cases of C14:0, C16:1, C18:1 and MUFA. In general, the new colouring approach allowed maintain the most relevant fatty acids unchanged.